Science and practice of strength training - Zatsiorsky, Vladimir M. PhD 1932- (Vladimir Mikhailovich); Fry, Andrew C. PhD 1956-; Kraemer, William J. PhD 1953- (Human Kinetics, 2021)
"Science and Practice of Strength Training addresses the complexity of strength training programs while providing advice in customizing programs for athletes and other populations. It covers velocity training, intensity, timing, exercises, injury prevention, overtraining, and athlete monitoring"--Provided by publisher